DESKRIPSI PARAMETER CUACA DAN STABILITAS UDARA TERKAIT KEJADIAN ANGIN PUTING BELIUNG PONTIANAK (STUDI KASUS 30 AGUSTUS 2016) - Andreas Kurniawan Silitonga; Immanuel Jhonson Arizona Saragin; Rino Wijatmiko Saragih (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2017)
On Tuesday, August 30th 2016 at 08.00 UTC, a tornado was occured in Pontianak, West Kalimantan. According to BNPB, on Indonesia tornado hazard index maps, Pontianak is an area  with a low potential of  tornadoes. The study is using an analytical description method for the meteorological data before and when tornado occurred. Pressure and air temperature for two days before tornado was occurred has the same pattern, but there is an anomaly when tornado occurred. Air temperature's pattern shows decline significantly from an hour before tornado was occurred that the value is 8,2 oC. Analysis of surface wind shows that wind velocity when tornado occurred is higher than 2 days before, with an anomaly of 11 knots. LI index shows that atmospheric stability is in stable condition. KI index shows medium potential of convective and the value is higher than 2 days before. TT index shows strong convective and the value is higher than 2 days before. SWEAT shows low potential of convective with stability value higher than 2 days before. CAPE shows strong potential of convective. Interpretation and analysis of satellite show the strong development of convective cloud and potentially causing a tornado in Pontianak at 08.00 UTC. So it can be concluded that when tornado occurred, atmospheric condition is unstable and there are Cb clouds which have Overshooting Top.Keywords: index of atmospheric liability, tornado, Pontianak.